Using a look-up table technique and finite element calculations for quick detection of stiff inclusions in silicone rubber. Issue 6 (7th February 2020) - Jonsson, Ulf G.; Lindahl, Olof A.; Andersson, Britt M.
Abstract : Purpose: The aim of the study was to show that a new method, using a look-up table technique, can be used to detect the presence and position of an inclusion embedded in a tissue-like material. Due to the time-consuming nature of the finite element (FE) method or FEM, real-time applications involving FEM as part of a control loop, are traditionally limited to slowly varying systems. By using a simplified two-dimensional FE model and a look-up table, we show by simulations and experiments that it is possible to achieve reasonable computational times in a tactile resonance sensor application. Design/methodology/approach: A piezoelectric disk was placed in the center of a silicone rubber disk (SRD) with viscoelastic properties, where it acted as both sensor and actuator and dissipated radial acoustic waves into the silicone. The look-up table was constructed by calculating the radial Lamb wave transition frequencies in the impedance frequency response of the sensor while varying the position of an inclusion. A position-matching algorithm was developed that matched measured and calculated Lamb wave transitions and thereby identified the presence and position of an inclusion. Findings: In an experiment, the position of a hard inclusion was determined by measuring the Lamb transition frequencies of the first radial resonance in two SRDs. The result of the matching algorithm for Disk 1 was that the matched position was less than 3% from the expected value. For Disk 2, the matching algorithm erroneously reported two false positions before reporting a position that was less than 5% from the expected value. An explanation for this discrepancy is presented. In a verifying experiment, the algorithm identified the condition with no inclusion present. Originality/value: The approach outlined in this work, adds to the prospect of developing time-sensitive diagnostic instruments. This approach has the potential to provide a powerful technique to quickly present spatial information on detected tumors.